Bio-ecological and cultural perspectives on sustainable healthy diets. A literature review - Akifa Laila Rusyda; Yayuk Farida Baliwati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Sustainable Healthy Diets (SHD) are understood to improve individual health while reducing environmental pressures; however, the integration of biological, ecological, and cultural dimensions remains insufficiently explored. This review aimed to describe SHD practices from these three perspectives to address gaps in knowledge regarding their bio-ecological and cultural interconnections. Methods: A literature review was conducted in March–April 2024 on English-language articles published between 2010 and 2024. Searches were performed in MDPI, PubMed, Science Direct, and The Lancet Planetary Health using the PECOS criteria. Of the 2,443 articles identified, 332 duplicates were removed, and 1,937 articles were excluded based on the inclusion criteria, leaving 174 articles for full-text assessment. The results showed that the SHD encompassed several dietary models, including local food–based diets, the Mediterranean diet, and the Planetary Health Diet, all of which emphasized plant-based choices. Biologically, SHD is associated with a reduced risk of non-communicable diseases, greater longevity, and adequate nutrient intake. Ecologically, SHD contributes to lower greenhouse gas emissions, reduced carbon and water footprints, and encourages food waste reduction. Culturally, SHD reflects moral values related to animal welfare, belief systems, veganism, and religious practices. In conclusion, this review highlights the importance of integrating biological, ecological, and cultural considerations to strengthen SHD implementation. This study supports evidence-based dietary recommendations and accelerates the transition toward healthier and more sustainable global food systems.